Current structures associated with dipolarization fronts. Issue 11 (8th November 2013) - Yao, Zhonghua; Sun, W. J.; Fu, S. Y.; Pu, Z. Y.; Liu, Jiang; Angelopoulos, V.; Zhang, X.‐J.; Chu, X. N.; Shi, Q. Q.; Guo, R. L.; Zong, Q.‐G.
Abstract [1] Recently, observational results on currents around the dipolarization fronts (DFs) of earthward flow bursts have attracted much research attention. These currents are found to have close association with substorm intensifications. This paper devotes to further study of the current system ahead and within the DFs with high‐resolution magnetic field measurements from Cluster constellation in 2003. The separation of four spacecraft is much smaller than the scales of spatial structures ahead and within the DF layer so that the currents can be reliably obtained. Based on features of the magnetic field variations prior to the fronts, we categorized the DFs into two types: DFs with magnetic dips immediate ahead of the fronts (type I) and DFs without magnetic dips (type II). For type I DFs, it is found that dawnward currents along the DFs exist in the dip region; duskward currents exist within the fronts. Furthermore, the dawnward currents in the dip region are found to be mainly parallel to the local magnetic field with a spatial scale of 1000 km, whereas the duskward currents within the fronts have both significant parallel and perpendicular components. On the other hand, for type II DFs, only significant duskward and mainly perpendicular currents show up within the fronts; no dawnward currents exist ahead of DFs. The dawnward and mainly parallel current in the type I DFs is important in the current coupling process between magnetosphere and ionosphere and may lead to local current disruptions for substorm initiations.